Low Brachial Artery Flow-Mediated Dilation Predicts Worse Prognosis in Hospitalized Patients with COVID-19 - Vanessa Bianconi (MDPI AG, 2021)
Background: Endothelial injury can be induced by coronavirus disease 2019 (COVID-19) and seems to exert a crucial pathogenic role in its most severe clinical manifestations. We aimed to investigate the association between brachial artery flow-mediated dilation (bFMD), a potential clinical and non-invasive measure of endothelial function, and in-hospital prognosis of COVID-19 patients. Methods: Brachial artery flow-mediated dilation was assessed in hospitalized COVID-19 patients within 48 h of hospital admission. The association between bFMD and either intensive care unit (ICU) admission or in-hospital death was explored using univariable and multivariable analyses. Results: Four hundred and eight patients were enrolled. Significantly lower bFMD values emerged in COVID-19 patients with either radiographic signs of pneumonia, respiratory distress, or the need for non-invasive ventilation compared with patients without these signs (p < 0.001, p = 0.001, and p < 0.001, respectively). Forty-two (10%) patients were admitted to the ICU, 76 (19%) patients died, and 118 (29%) patients met the composite endpoint of ICU admission/in-hospital death. At unadjusted Cox regression analysis showed that low bFMD (<4.4%, the median value) was associated with a higher risk for the composite endpoint of ICU admission/in-hospital death compared with high bFMD (≥4.4%, the median value) (HR 1.675, 95% CI 1.155–2.428, p = 0.007). Multi-adjusted Cox regression analyses showed that low bFMD was independently associated with a 1.519- to 1.658-fold increased risk for the composite endpoint of ICU admission/in-hospital death. Conclusions: Low bFMD predicts an unfavorable in-hospital prognosis in COVID-19 patients. The measurement of bFMD may be clinically useful in the prognostic stratification of COVID-19 patients upon hospital admission.